Exploration study of user relevance judgement of web documents. - Chan, Chwee Fong. (2008)
In the face of the information explosion fuelled by the phenomenal growth of the Web, researchers are increasingly turning to information systems based on user relevance feedback for the answer to better retrieval tools, making research on user relevance especially timely. This research is an attempt to provide some insight into the way the user makes relevance judgement.